2019
DOI: 10.1002/jaal.986
|View full text |Cite
|
Sign up to set email alerts
|

Foregrounding Collaboration in Disciplinary Literacy: Implications From JAAL, 2008–2017

Abstract: In this review, the authors examined articles on collaboration within the context of disciplinary literacy that appeared in the Journal of Adolescent & Adult Literacy between October 2008, when Moje published “Foregrounding the Disciplines in Secondary Literacy Teaching and Learning: A Call for Change,” and December 2017. Findings suggest that the definition of disciplinary literacy has expanded, collaboration is important for both teacher and student learning, and tension surfaces when collaboration happens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…As Takeuchi et al (2020) remind us, the views on transdisciplinarity depend on the ideologies and worldviews we chose to employ. In the context of this study, we have a strong commitment to content knowledge and the importance of existing curricula, whereas other ways of dealing with transdisciplinarity start from more holistic approaches based on individual student experiences (Osborne, 2015). Educating and empowering youth to be active, engaged, positive, and globally connected citizens require that we reposition education as a creative and diverse endeavor where epistemological differences are valued (Burnard et al, 2022).…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…As Takeuchi et al (2020) remind us, the views on transdisciplinarity depend on the ideologies and worldviews we chose to employ. In the context of this study, we have a strong commitment to content knowledge and the importance of existing curricula, whereas other ways of dealing with transdisciplinarity start from more holistic approaches based on individual student experiences (Osborne, 2015). Educating and empowering youth to be active, engaged, positive, and globally connected citizens require that we reposition education as a creative and diverse endeavor where epistemological differences are valued (Burnard et al, 2022).…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Content literacy generally refers to implementing various stand-alone strategies to help students understand text in subject-matter courses (Shanahan & Shanahan, 2012). In their review of the literature, Hinton and Suh (2019) found that the definition of literacy is expanding to include other subject areas such as the arts and physical education and consideration of digital literacies. The expansion consists of effective engagement with digital textbooks and evaluating digital tools and resources used by experts and practitioners in the discipline field (i.e., biologists, chemists).…”
Section: Content Literacymentioning
confidence: 99%
“…The expansion consists of effective engagement with digital textbooks and evaluating digital tools and resources used by experts and practitioners in the discipline field (i.e., biologists, chemists). Hinton and Suh (2019) posit that an expansive view of content literacy can encourage teachers to broaden their perspective to consider digital literacies and expand the pool of disciplines with which to collaborate.…”
Section: Content Literacymentioning
confidence: 99%
“…Disciplinary literacy practices are multifaceted and have been conceptualized in a variety of ways (Hinton & Suh, 2019). Like Moje (2015), we conceive of these practices as existing at the intersection of epistemological, cognitive, linguistic, and cultural factors associated with specific disciplines, while also recognizing the interdisciplinary nature of certain literacy practices (Hauseal et.…”
Section: Enactments Of Disciplinary Literacy Practices In Youth Built Change: Believing Knowing Doing and Communicatingmentioning
confidence: 99%
“…Collaboration—among teachers, between teachers and disciplinary experts, and among students—is critical to disciplinary approaches to literacy learning (Hinton & Suh, 2019). Collaborative teams might involve university faculty working alongside graduate students or pre‐service teachers, as well as teachers who provide specific instructional support (e.g., Intervention Specialist or ESL teacher).…”
Section: Implications For Teachers: Supporting Enactments Of Disciplinary Literacymentioning
confidence: 99%